Migration flows in the Mediterranean numbers, politics and multiple crises - Alessio D’Angelo (Anuario CIDOB de la Inmigración, 2018)
Migration across the Mediterranean is often presented – in media and political debates – as a single, transnational phenomenon characterised by steady inflows of people, and seemingly guided by uncontrollable forces. By examining official statistics for the 2014 – 2018 period, this paper aims to present an alternative narrative. It compares different sub-regional scenarios – particularly focusing on Greece, Italy and Spain as countries of arrival – and their variations over time, looking at sea arrivals, search and rescue and death-at-sea data. In doing so, it highlights the complexity of a multiplicity of “refugee crises”, but also the major role played by national governments and other international actors not just in shaping migration flows but also in determining their humanitarian impact.